1974
DOI: 10.1002/oms.1210090403
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric studies of diterpenes: VIII—Epimers

Abstract: Diterpene epimers differing with respect to orientation of a secondary hydroxyl group, ring fusion or configuration at an asymmetric centre carrying carbon-carbon linked substituents were studied, and certain stereostructural-spectral correlations were achieved for the first two groups. Each of the compounds examined was subjected to multiple scanning at both high and low electron voltage to allow computer assisted statistical calculation and comparison of intensity intervals at a predetermined confidence leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
1977
1977

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In two of these studies various epimeric diterpene alcohols were utilized as substrates, and it was concluded that both cis 1,3-and cis 1,4-eliminations occurred stereospecifically provided that the hydrogen abstracted was tertiary. 1233 in the other study, water elimination from some adamantane derivatives was investigated.1234 Water loss has also been noted from various other molecular structures, including acetylated 2,2'-diaminodiphenylmethanes,1235 phthalazinone derivatives,1236 the m/e 99 fragment ion of dialkyl phosphates,1237 a fragment ion from certain 4,6-diaikyl-1,3dioxanes,1238 and the (M -CH3)+ fragment ion of ethyl 2ethoxybenzoate.1239 In addition, the unusual loss of HO• from various bipiperidyl alkaloids containing an amide function has been studed in detail. 1240 The loss of methanol from 4-fezt-butylcyclohexyl methyl ether under photoionization conditions occurs more readily from the trans isomer which also has the more abundant molecular ion; a 1,4-mechanism is proposed for this elimination.…”
Section: Addendummentioning
confidence: 99%
“…In two of these studies various epimeric diterpene alcohols were utilized as substrates, and it was concluded that both cis 1,3-and cis 1,4-eliminations occurred stereospecifically provided that the hydrogen abstracted was tertiary. 1233 in the other study, water elimination from some adamantane derivatives was investigated.1234 Water loss has also been noted from various other molecular structures, including acetylated 2,2'-diaminodiphenylmethanes,1235 phthalazinone derivatives,1236 the m/e 99 fragment ion of dialkyl phosphates,1237 a fragment ion from certain 4,6-diaikyl-1,3dioxanes,1238 and the (M -CH3)+ fragment ion of ethyl 2ethoxybenzoate.1239 In addition, the unusual loss of HO• from various bipiperidyl alkaloids containing an amide function has been studed in detail. 1240 The loss of methanol from 4-fezt-butylcyclohexyl methyl ether under photoionization conditions occurs more readily from the trans isomer which also has the more abundant molecular ion; a 1,4-mechanism is proposed for this elimination.…”
Section: Addendummentioning
confidence: 99%